Co3O4/TiO2 heterostructures obtained by hybrid method. Issue 7 (29th April 2015) - El Habra, N.; Visentin, F.; Gerbasi, R.; Favaro, M.; Natile, M. M.; Colazzo, L.; Sambi, M.
<x xml:space="preserve">Abstract</x> High surface‐to‐volume ratio Co3O4/TiO2 heterojunctions were fabricated by combining different methods. Atomic layer deposition (ALD) and a photochemical method were used to coat polystyrene (PS) 3D‐Direct Opal (3D‐DO) structures on conductive ITO substrates. Firstly, 3D‐DO of PS were crystallized on ITO substrates to form the high surface‐to‐volume ratio template via a self‐assembly method. A low‐temperature ALD TiO2 film was infiltrated onto the PS opal structure. Then, the PS template was removed by a thermal treatment in air at 450 °C for 5 h. Hollow anatase phase nanospheres were obtained, crystallized in a face centered cubic (FCC) lattice with the (111) plane oriented parallel to the substrate surface. Finally, the hollow TiO2 nanospheres were coated with Co3O4 via a photochemical method. This ordered 3D nanostructure with designed morphology may find applications as surface‐enhanced materials for photovoltaic devices. <inline-graphic xlink:href="ark:/27927/pgj1m9pmr13" content-type="pssa201532260-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> TiO2 hollow nanospheres obtained via low‐pressure ALD (a) and Co3O4/TiO2 heterostructure (scanned region: 1.5 μm) (b).